The Influence of Various Plasma Components on the Lysis of Dilute Human Blood Clots - Gallimore, M. J; Shaw, J. T. B (Thrombosis and Haemostasis, 1969)
The influence of various plasma components on the lysis of dilute blood clots has been investigated. Blood from normal subjects was diluted with 0.12 M sodium acetate and the component being investigated was added; the clots which formed on the addition of thrombin were incubated and their lysis was observed. Fibrinogen and factor XIII were found to retard clot lysis. Plasminogen activator accelerated lysis, and the serum antiplasmins and plasminogen had only marginal effects at the concentrations studied. The significance of the dilute blood clot lysis assay is discussed in the light of these observations.